2009
DOI: 10.1371/journal.pone.0004481
|View full text |Cite
|
Sign up to set email alerts
|

Age and Diet Affect Gene Expression Profile in Canine Skeletal Muscle

Abstract: We evaluated gene transcription in canine skeletal muscle (biceps femoris) using microarray analysis to identify effects of age and diet on gene expression. Twelve female beagles were used (six 1-year olds and six 12-year olds) and they were fed one of two experimental diets for 12 months. One diet contained primarily plant-based protein sources (PPB), whereas the second diet contained primarily animal-based protein sources (APB). Affymetrix GeneChip Canine Genome Arrays were used to hybridize extracted RNA. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 78 publications
5
14
0
Order By: Relevance
“…It has also been reported that WFDC2 is involved in inflammatory responses and host defense, and its activity is increased in chronically inflamed lungs with cystic fibrosis [12]. Increased expression of genes related to inflammation and immune response was also observed in other tissues from these dogs [6], [7], [8]. In our previous experiment [4], senior dogs fed APB had a greater concentration of blood cholesterol than those fed PPB diet.…”
Section: Discussionsupporting
confidence: 68%
“…It has also been reported that WFDC2 is involved in inflammatory responses and host defense, and its activity is increased in chronically inflamed lungs with cystic fibrosis [12]. Increased expression of genes related to inflammation and immune response was also observed in other tissues from these dogs [6], [7], [8]. In our previous experiment [4], senior dogs fed APB had a greater concentration of blood cholesterol than those fed PPB diet.…”
Section: Discussionsupporting
confidence: 68%
“…Hybridization reactions were performed with reagents f in accordance with the manufacturer' s instructions and as previously described. 17 After hybridization, microchips were washed and stained with a streptavidin-conjugated phycoerthyrin dye enhanced with biotinylated goat anti-streptavidin antibody via a wash and stain station g and associated software. Images of microchips were acquired by use of a scanning system.…”
Section: Methodsmentioning
confidence: 99%
“…To identify the molecular mechanisms underlying sarcopenia, several groups have performed whole-genome expression analysis of skeletal muscle during aging at the transcriptional level in rodents (Lee et al 1999;Pattison et al 2003), monkeys (Kayo et al 2001), dogs (Middelbos et al 2009) and humans (Bortoli et al 2003;Dennis et al 2008;Giresi et al 2005;Jozsi et al 2000;Melov et al 2007;Roth et al 2002;Welle et al 2000Welle et al , 2003Welle et al , 2004Zahn et al 2006). Large numbers of genes, ranging from tens to hundreds (typical) to thousands, have been shown to undergo age-associated alterations in transcription levels.…”
Section: Gene Expression Microarray Studiesmentioning
confidence: 99%